Perception of psoriasis treatment in the outpatient setting: survey of patients and their prescribing physicians. (3rd April 2017) - Carrascosa, J. M.; de la Cueva, P.; Herranz, P.; Labandeira, J.; Notario, J.
Abstract: Background: Patients' perception of disease management can influence compliance to treatment and thus affect outcome. Objective: To survey patients and physicians on their perceptions of biologic therapy for treating psoriasis in an outpatient setting. Methods: The subjective impact of intravenous treatment of severe psoriasis on patients and physicians in the outpatient setting was determined via two surveys. Results: Between September and November 2014, 24 dermatologists and 90 patients were surveyed. Treatment with biologic agents in the outpatient setting was associated with a high level of patient satisfaction: 93.3% of patients considered their psoriasis well controlled and 46.1% reported complete control. Patients highly valued the feeling of greater disease control (72.2%), regular follow-up (66.7%) and rapid improvement of psoriasis (58.9%) when attending an outpatient setting. Other positive aspects of outpatient treatment were control of other health issues and perceived improvements in quality of life (QoL). Outpatient attendance was high; with 90% of patients keeping scheduled appointments and 79.2% of physicians acknowledged that they were able to monitor their patients' condition more closely. Conclusion: Administration of treatment in an outpatient setting may provide a feeling of improved QoL and disease control.